2018
DOI: 10.1128/aac.00030-18
|View full text |Cite
|
Sign up to set email alerts
|

Integrase-Mediated Recombination of the bel-1 Gene Cassette Encoding the Extended-Spectrum β-Lactamase BEL-1

Abstract: Integrons are genetic elements that can acquire and rearrange gene cassettes. The gene encodes an extended-spectrum β-lactamase, BEL-1, that is present at the second position of the variable region of class 1 integrons identified in The mobility of the gene cassette was analyzed under physiological conditions and with the integrase gene being overexpressed. Cassette mobility in was detected by excision/integration into the recipient integron In on the conjugative plasmid R388 with the overproduced integrase. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…The second notable feature is the type 3 integrase carrying bla BEL-1 that we found in our isolates, which is also present in the previous C. freundii and K. pneumoniae isolates. To date, the bla BEL-1 has usually been found in cassettes with class 1 integrons in P. aeruginosa (Bouheraoua et al 2018 ) , and had only been observed associated with the class 3 integrase in the previously reported K. pneumoniae isolate from Portugal (Papagiannitsis et al 2015 ). The class 3 integrase is not frequent in collections of multidrug-resistant isolates and has not been detected in isolates from healthy volunteers in Spain (Vinué et al 2008 ) or in a population-based study in France (Laroche et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second notable feature is the type 3 integrase carrying bla BEL-1 that we found in our isolates, which is also present in the previous C. freundii and K. pneumoniae isolates. To date, the bla BEL-1 has usually been found in cassettes with class 1 integrons in P. aeruginosa (Bouheraoua et al 2018 ) , and had only been observed associated with the class 3 integrase in the previously reported K. pneumoniae isolate from Portugal (Papagiannitsis et al 2015 ). The class 3 integrase is not frequent in collections of multidrug-resistant isolates and has not been detected in isolates from healthy volunteers in Spain (Vinué et al 2008 ) or in a population-based study in France (Laroche et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%